Professional competences and international certifications of accounting area (Journal of Management & Business, 2021)
Historically, the practice of professional accounting is recognized for control access and exercise, in order to certify the candidate in the area. Internationally, responding to the needs of auditing companies, associations were formed with the aim of accrediting candidates who propose to exercise the function. Nowadays, with accounting harmonization, greater access to information and the possible transit of professionals between countries, have led young people to submit to international certifications in search of international career opportunities or even for their professional development in Brazil. The article aims to analyze recent exams by international certifying entities CPA – Certified Public Accountant, CMA – Certified Management Accountant and ACCA – Association of Chartered Certified Accountants, from the perspective of professional competences in relation to Le Boterf’s list of competences, integrated into the Taxonomy structure of Bloom. The adoption of international standards, most notably dictated by IFRS – International Financial Report Standards, requires students and professionals to submit to exams promoted by internationally recognized certifying entities for the full exercise of their attributions with a view to a successful career. Thus, through documentary research carried out in the previous tests, CMA 2017, CPA 2019 and ACCA 2020, based on the models mentioned, the level of demand and related competences were traced, which can serve as a guide for future candidates. The results reveal that the most demanded skills are those that address intellectual and technical perspectives. From the analyzed material, 75% of the questions are structured for single answers and 25% for essay answers. It was observed that 64% of the questions fall into intermediate levels of Bloom’s Taxonomy: apply and analyze. International exams compared to Brazilian exams are at a higher level of complexity, requiring preparation at adequate levels.
Keywords: Accounting; Le Boterf; Bloom’s Taxonomy; International Accounting Certification